Zeros da função zeta de Riemann e o teorema dos números primos - Oliveira, Willian Diego [UNESP] (2013)
We studied various properties of the Riemann’s zeta function. Three proofs of the Prime Number Theorem were provides. Classical results on zero-free region of the zeta function, as well as their relation to the error term in the Prime Number Theorem, were studied in details